Correcting Middle School Students' Misunderstandings Using the CLIS Model on Temperature, Heat, and Expansion Material - Andini Febriani; Khairil Arif; Fakhri Syafitra (Postgraduate, University of Mataram, 2026)
Students' misconceptions in science learning, particularly on temperature, heat, and expansion, are still frequently found in junior high school and have the potential to influence the development of an accurate understanding of scientific concepts. This situation indicates the need for the implementation of a learning model oriented towards conceptual change. Therefore, this study aims to analyze the effectiveness of the Children's Learning in Science (CLIS) model in remediating misconceptions among seventh-grade students at the UNP Laboratory Development School. This study was a pre-experimental study with a one-group pretest-posttest design involving 25 students. Data were collected through a diagnostic test to identify misconceptions, observation sheets on the implementation of the learning model, and student response questionnaires. Data were analyzed using the Decrease of Quantitative Misconception (DQM) index and the McNemar test using SPSS. The results showed that the average percentage of student misconceptions decreased from 23% in the pretest to 10% in the posttest, while the percentage of students who understood the concepts increased from 14% to 54%. The CLIS model was implemented well, with an average learning model implementation score of 73%. The DQM analysis showed the effectiveness of remediation in the moderate category, with an average score of 59%. The McNemar test obtained an Asymp.Sig. value of 0.000 with a significance level of α = 0.05, indicating a significant difference between student conceptions before and after the learning process. Furthermore, the questionnaire results showed that 71% of students responded well. Thus, the CLIS model was effective in producing significant changes in conceptions and received positive responses, thus having implications for improving the quality of science learning.